Guided imagery relaxation technique : its effect on stress and well-being of primary school children in Kubang Kerian - Wei, Lim Chean (2021)
With the global pandemic of COVID-19 circling around the world population since the beginning of 2020, to learn effective coping with negative emotional and behavioural experiences is especially a concern to the children and adolescents, who face restrictions on their physical movement and to do virtual learning at home. Therefore, there is a crucial need to study the effect of mindfulness-based approach, guided imagery relaxation technique on stress and well-being of the elementary school children. A randomized controlled trial study, pretest-posttest with a waitlist control group was designed to examine the objective stated above. Thirty-four Standard Five Al-Biruni and Al-Farabi students of Sekolah Kebangsaan Kubang Kerian II (SKKK-II) participated in current study and were randomly assigned to intervention (N=17) or waitlist-control (N=17) groups. The participants from intervention group were required to attend four consecutive weekly monitoring session and practise to the audio guided imagery relaxation technique on daily basis. The children and their caregivers successfully completed the Stress in Children (SiC) Questionnaire, Strengths and Difficulties Questionnaire - Parent Reported (SDQ-PR) and tracking form across preand post-intervention time points. Result from mixed-model ANOVA indicated that there was no significant difference observed in stress and well-being between participants from treatment and waitlist-control groups across pre- and post-intervention time points, with both p values more than .05. The insignificance of result could possibly be discussed from four different factors: time availability, drop-out and adherence rates, Internet accessibility and connectivity, and differences in between making physical and virtual contact. Several useful implications and limitations of current study as well as recommendations for future studies are being explored to gain insights about the result of present study and add up the mindfulness-based intervention-related experience to fill in the existing gap of knowledge.